Malawi : Sixth and Final Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Nonobservance of Performance Criteria and Augmentation Access; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report, 2008)
This paper discusses key findings of the Sixth and Final Review for Malawi Under the Poverty Reduction and Growth Facility (PRGF). Performance remained generally strong in the period under review. The authorities met most program targets for end-December 2007, and domestic debt fell as a share of GDP, but the domestic borrowing performance criterion was missed. The government aims to meet the 2007/08 domestic borrowing target. Higher fuel and fertilizer prices are putting pressure on international reserves, which are down from an already inadequate level.